2006
DOI: 10.1002/anie.200601259
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Tubulysin U and V

Abstract: Tubulysins (1) are compounds of extraordinary potency, rapidly degrading the tubulin cytoskeleton, with tubulysin D being the most active tubulin-modifier known so far.[1, 2] The tubulysins were first described by Höfle, Reichenbach, and co-workers in 2000. [3,4] Several representatives are active with GI 50 values (growth inhibition of 50 %) in the low picomolar range against the NCI-60 cancer cell-line panel, and some are highly antiangiogenic.[5] Semisynthetic tubulysins, derived from isolated material, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 19 publications
1
43
0
1
Order By: Relevance
“…We were gratified to find that treatment of tripeptide 15 with the ( S )-CBS or ( R )-CBS reagent in the presence of BH 3 •DMS almost exclusively afforded the reduced tripeptides 16 and 17 , respectively (Schemes 3 and 4). The stereochemical outcome of these reactions was supported by the following: 1) the 1 H NMR spectrum of 4 matched that of tubulysin V as previously reported, 5a and 2) the findings of Zanda and co-workers who reported that the ( S )-CBS reagent with BH 3 •DMS reacted nearly exclusively from the si face of the ketone of a racemic Tuv intermediate to give the alcohol products possessing the natural configuration as established by X-ray crystallography. 5a The 1 H NMR spectrum of the immediate tetrapeptide benzyl ester precursor of tubulysin V was identical to the minor diastereomer 14 , enabling us to assign the stereochemistry of the purified diastereomers 14 .…”
supporting
confidence: 77%
See 2 more Smart Citations
“…We were gratified to find that treatment of tripeptide 15 with the ( S )-CBS or ( R )-CBS reagent in the presence of BH 3 •DMS almost exclusively afforded the reduced tripeptides 16 and 17 , respectively (Schemes 3 and 4). The stereochemical outcome of these reactions was supported by the following: 1) the 1 H NMR spectrum of 4 matched that of tubulysin V as previously reported, 5a and 2) the findings of Zanda and co-workers who reported that the ( S )-CBS reagent with BH 3 •DMS reacted nearly exclusively from the si face of the ketone of a racemic Tuv intermediate to give the alcohol products possessing the natural configuration as established by X-ray crystallography. 5a The 1 H NMR spectrum of the immediate tetrapeptide benzyl ester precursor of tubulysin V was identical to the minor diastereomer 14 , enabling us to assign the stereochemistry of the purified diastereomers 14 .…”
supporting
confidence: 77%
“…Interestingly, purification of tubulysin V by reverse-phase HPLC under the conditions reported by Dömling and co-workers 5b using MeOH as the mobile phase resulted in isolation of the methyl ester to a significant extent (38%). Using acetonitrile as the mobile phase smoothly afforded the natural product in an analytically pure form.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…D-Mep (8) and L-Ile-OMe (10) were synthesized in parallel. Reductive amination using formaldehyde and commercially available pipecolic acid (7) proceeded smoothly to give D-Mep (8) in a quantitative yield, and the esterification of L-Ile (9) in methanol afforded L-Ile-OMe (10) in a good yield (75%) as well. D-Mep (8) and L-Ile-OMe (10) were then coupled together.…”
Section: Letter Syn Lettmentioning
confidence: 98%
“…The Ugi-4CR is not specifically prone to asymmetric induction, but at least some auxiliaries are known to result in preferential formation of a diastereoisomer [3334]. Therefore, the isonitrile 4b was synthesized from menthyl anthranilate.…”
Section: Resultsmentioning
confidence: 99%